Gender, social involvement, and life satisfaction of retired government employees in Miag-ao, Iloilo - Gallaza, Rica F.
This research study investigated the life satisfction, social involvement, and the relationship of both variables of retired individuals. Respondents of the study are 74 retired government employees in Miagao. Thirty three (33) of them were males and forty one (41) were females whose ages ranged from 55 to 70 or those who have retired for not more than 5 years at the time of the study. Participants completed a series of questionnaires to measure the vriables under study. Researchers used a corrrelational design to examine the data gathered. In analyzing the results, mean and standard deviation of both genders were calculated to show the level of life satisfactionand social involvement of the samples. Pearson rcorrelation, on the other ahnd, wa also used to analyze the relationship between variables of both genders. From the data collected, it was revealed that women were slightly more socailly involved in activities in their communities than men were. It was also shown that both genders have average social involvement. Likewise, the study also found out that there was no significant difference between genders in their life satisfaction. In fact, both male and female respondents indicated same level of satisfaction with their lives. Generally, their scores fall on the slightly satisfied continuum. Relationship of lfie satisfaction and social involvement between genders showed weak correlation and ahd a statistically insignificant difference. Result in the social involvement and life satisfaction relationship among retirees in the study, in general, is identified having a weak to moderate correlation.